2011
DOI: 10.1126/science.1202663
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of RNA Polymerase II Is Modified by Site-Specific Methylation

Abstract: The carboxy-terminal domain (CTD) of RNA polymerase II (RNAPII) in mammals undergoes extensive posttranslational modification, which is essential for transcriptional initiation and elongation. Here, we show that the CTD of RNAPII is methylated at a single arginine (R1810) by the coactivator-associated arginine methyltransferase 1 (CARM1). Although methylation at R1810 is present on the hyperphosphorylated form of RNAPII in vivo, Ser2 or Ser5 phosphorylation inhibits CARM1 activity toward this site in vitro, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
221
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(225 citation statements)
references
References 16 publications
3
221
0
1
Order By: Relevance
“…In addition to transcriptional activation, CARM1 methylates splicing factors (32), modulates recognition of 5′ splicing sites (33), and regulates the coupling of transcription and splicing (34). Furthermore, a recent report showed that RNAPII carboxyl-terminal domain is methylated by CARM1 (35). Mutating the CARM1 methylation site in RNAPII carboxylterminal domain affects snoRNA expression similar to the effect observed in CARM1 −/− mouse embryonic fibroblast cells (35).…”
Section: Paf1c and Carm1 Coordinately Regulate A Common Set Of Erαmentioning
confidence: 83%
“…In addition to transcriptional activation, CARM1 methylates splicing factors (32), modulates recognition of 5′ splicing sites (33), and regulates the coupling of transcription and splicing (34). Furthermore, a recent report showed that RNAPII carboxyl-terminal domain is methylated by CARM1 (35). Mutating the CARM1 methylation site in RNAPII carboxylterminal domain affects snoRNA expression similar to the effect observed in CARM1 −/− mouse embryonic fibroblast cells (35).…”
Section: Paf1c and Carm1 Coordinately Regulate A Common Set Of Erαmentioning
confidence: 83%
“…130 In addition to the interaction of SMN with R1810me2s, SMN interacts with senataxin (SETX) (Fig. 3A).…”
Section: Smn and Transcriptional Regulationmentioning
confidence: 99%
“…These modifications suggest a dual gradient model for increasing Ser2 and decreasing Ser5 phosphorylation across genes that regulate transcription 3,4 . In addition to these serine phosphorylations, arginine methylation at one specific residue of the CTD was shown to lead to misregulation of snRNAs as well as small nucleolar RNAs expression 21 .…”
mentioning
confidence: 99%